High‐Efficiency Solution‐Processed Two‐Terminal Hybrid Tandem Solar Cells Using Spectrally Matched Inorganic and Organic Photoactive Materials. Issue 37 (2nd September 2020) - Aqoma, Havid; Imran, Imil Fadli; Wibowo, Febrian Tri Adhi; Krishna, Narra Vamsi; Lee, Wooseop; Sarker, Ashis K.; Ryu, Du Yeol; Jang, Sung‐Yeon
Abstract: Although the power conversion efficiency (PCE) of inorganic perovskite‐based solar cells (PSCs) is considerably less than that of organic‐inorganic hybrid PSCs due to their wider bandgap, inorganic perovskites are great candidates for the front cell in tandem devices. Herein, the low‐temperature solution‐processed two‐terminal hybrid tandem solar cell devices based on spectrally matched inorganic perovskite and organic bulk heterojunction (BHJ) are demonstrated. By matching optical properties of front and back cells using CsPbI2 Br and PTB7‐Th:IEICO‐4F BHJ as the active materials, a remarkably enhanced stabilized PCE (18.04%) in the hybrid tandem device as compared to that of the single‐junction device (9.20% for CsPbI2 Br and 10.45% for PTB7‐Th:IEICO‐4F) is achieved. Notably, the PCE of the hybrid tandem device is thus far the highest PCE among the reported tandem devices based on perovskite and organic material. Moreover, the long‐term stability of inorganic perovskite devices under humid conditions is improved in the hybrid tandem device due to the hydrophobicity of the PTB7‐Th:IEICO‐4F back cell. In addition, the potential promise of this type of hybrid tandem device is calculated, where a PCE of as much as ≈28% is possible by improving the external quantum efficiency and reducing energy loss in the sub‐cells. Abstract : High‐efficiency solution‐processed hybrid tandem photovoltaic devices, employing inorganic perovskite and organic bulk‐heterojunction as the photoactive layers, are demonstrated. A PCE of 18.04% in the hybrid tandem device is achieved, which is significantly higher than the comparable single‐junction devices, owing to a near‐optimal absorption spectral match.